Heavy Metals in Soil Samples of Guntur Auto Nagar, Andhra Pradesh - Jyothi, M; Sudhakar, G; Brahmajirao, P (International Journal of Computer Sciences and Engineering, 2025)
The heavy metals in soil samples of Guntur auto nagar, Andhra Prdesh were analyzed using standard methodologies of soil analysis WHO and BIS, three sampling stations are studied in six months duration from February to July in the study area. The following metals were detected, Iron (Fe), Zinc (Zn), Chromium (Cr), Copper (Cu), Cadmium (Cd), Lead (Pb) and Nickel (Ni). Their minimum, maximum, average values (mg/kg-1) and standard deviation of three sampling stations were observed and the maximum values are recorded as follow Fe-131.05 mg/kg-1, Cr-1.91 mg/kg-1, Zn-98.37 mg/kg-1, Cu-69.9 mg/kg-1, Cd-9.31 mg/kg-1, Ni-14.32 mg/kg-1, according to the standard values in three sampling stations of soil samples exceeded due to improper sanitation and lack of rainfall the heavy metals are stored in soils.